Dancing on the Brexit cliff edge: The key to the exit negotiations lies in British domestic policy - Nicolai von Ondarza (Stiftung Wissenschaft und Politik (SWP), 2018)
The negotiations on the Brexit withdrawal agreement are heading for the endgame: An agreement is to be reached in October - at the latest in November 2018 - if the United Kingdom is to leave the EU in an orderly manner in March 2019, as planned. But the EU-27 and the British government are still a long way from reaching this agreement. Above all, British domestic policy is unpredictable: There is neither a majority for any form of Brexit, nor a substantial change of opinion against Brexit, as such. Any outcome of the Brexit negotiations threatens to trigger a political crisis in the UK, further increasing the risk of a disruptive exit..
Keywords: 320